A figure of merit for fast-charging Li-ion battery materials - Xia, Huarong (2022)
Rate capability is characterized necessarily in almost all battery-related reports, while there is no universal metric for quantitative comparison. Here, we proposed the characteristic time of diffusion, which mainly combines the effects of diffusion coefficients and geometric sizes, as an easy-to-use figure of merit (FOM) to standardize the comparison of fast-charging battery materials. It offers an indicator to rank the rate capabilities of different battery materials and suggests two general methods to improve the rate capability: decreasing the geometric sizes or increasing the diffusion coefficients. Based on this FOM, more comprehensive FOMs for quantifying the rate capabilities of battery materials are expected by incorporating other processes (interfacial reaction, migration) into the current diffusion-dominated electrochemical model. Combined with Peukert's empirical law, it may characterize rate capabilities of batteries in the future.